2021
DOI: 10.1097/rli.0000000000000800
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Magnetic Resonance Fingerprinting in Neonates

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
(116 reference statements)
2
15
0
Order By: Relevance
“…Measured values of CBF and relaxation time in most regions were correlated with corrected GA in our study. Regarding CBF, many studies have explored the associations between corrected GA and CBF 6,7,32 and between corrected GA and relaxation times, 12,13,15 and our study results are consistent with these previous findings. Cerebral blood flow has been seen to increase with corrected GA to reflect brain development 7 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Measured values of CBF and relaxation time in most regions were correlated with corrected GA in our study. Regarding CBF, many studies have explored the associations between corrected GA and CBF 6,7,32 and between corrected GA and relaxation times, 12,13,15 and our study results are consistent with these previous findings. Cerebral blood flow has been seen to increase with corrected GA to reflect brain development 7 .…”
Section: Discussionsupporting
confidence: 93%
“…7 Regarding relaxation times, T1 and T2 values decrease with age in childhood, which is prominent in the first 2 years of infancy. 12 In preterm neonates, T1 and T2 relaxation times have showed a negative relationship with corrected GA at MRI, 13,15 reflecting a general decrease in relaxation time with higher maturation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, relaxation values in each ROI were linearly and negatively correlated with GA, which was almost consistent with the results of the latest research that found that T1 relaxation value was linearly correlated with GA in the newborn brain by quantifying regional differences and maturation of the newborn brain using a 3D magnetic resonance fingerprint (Yu et al, 2022). In addition, we obtained a linear correlation between the T2 value and GA, which was not found by magnetic resonance fingerprinting.…”
Section: Limitationssupporting
confidence: 90%